2014
DOI: 10.1002/jbmr.2168
|View full text |Cite
|
Sign up to set email alerts
|

A 6-Year Exercise Program Improves Skeletal Traits Without Affecting Fracture Risk: A Prospective Controlled Study in 2621 Children

Abstract: Most pediatric exercise intervention studies that evaluate the effect on skeletal traits include volunteers and follow bone mass for less than 3 years. We present a population-based 6-year controlled exercise intervention study in children with bone structure and incident fractures as endpoints. Fractures were registered in 417 girls and 500 boys in the intervention group (3969 person-years) and 835 girls and 869 boys in the control group (8245 person-years), all aged 6 to 9 years at study start, during the 6-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(65 citation statements)
references
References 59 publications
4
59
2
Order By: Relevance
“…These contrasting results in terms of the effects of our SPE program on body composition are consistent with several previous reports which also observed mixed findings following schoolbased PA interventions. (8,(34)(35)(36) Nevertheless, the finding that the SPE program improved LM in girls is likely related to the fitness activities included in every specialist PE lesson plan, and not in usual PE, which emphasized static and dynamic balance activities that required isometric and dynamic muscular contractions, which may be considered a form of resistance training. The reason why there was no additional benefit on LM in boys that received the same program is unclear, but may relate to the fact that the girls were less habitually active at baseline (and throughout the study) (32) and/or that the boys may have engaged in more regular sport outside of school.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These contrasting results in terms of the effects of our SPE program on body composition are consistent with several previous reports which also observed mixed findings following schoolbased PA interventions. (8,(34)(35)(36) Nevertheless, the finding that the SPE program improved LM in girls is likely related to the fitness activities included in every specialist PE lesson plan, and not in usual PE, which emphasized static and dynamic balance activities that required isometric and dynamic muscular contractions, which may be considered a form of resistance training. The reason why there was no additional benefit on LM in boys that received the same program is unclear, but may relate to the fact that the girls were less habitually active at baseline (and throughout the study) (32) and/or that the boys may have engaged in more regular sport outside of school.…”
Section: Discussionmentioning
confidence: 99%
“…One school-based intervention that followed children aged 6 to 9 years at study start for 6 years showed that those involved in a nonspecific PE program (40 min daily) had greater bone accrual at the spine and femoral neck than controls who received the standard 60 min per week of PE; girls receiving daily PE also had larger tibial cross-sectional area at follow-up. (8) Although the PE lessons in this study were delivered by the usual classroom teacher, it has been reported that generalist classroom teachers have difficulties in effectively delivering quality PE lessons. (9) In addition, with the introduction of national assessments of literacy and numeracy in many countries, including Australia, there has been increased pressure on classroom teachers to focus on improving academic standards.…”
Section: Introductionmentioning
confidence: 96%
“…4 Several studies in childhood and young adults support a beneficial effect in this age group. [5][6][7] In the adult, long-term data are somewhat more limited. To our knowledge, there are only few long-term prospective studies.…”
Section: Physical Activity and The Bonementioning
confidence: 99%
“…A smaller study in Sweden also described that daily vigorous physical activity for at least 25 min seems to improve femoral neck bone strength in children [33] . In a population-based, 6-year, controlled exercise intervention study in children 6-9 years of age, daily physical exercise improved bone mass and bone size in girls, and bone mass in boys, without affecting the fracture risk [34] . A large study in the United Kingdom evaluated 1,748 boys and girls (mean age 15.5 years), and investigators found that vigorous day-to-day physical activity is associated with indices of cortical bone mass and geometry in adolescents, whereas light or moderate physical activity has no detectable association.…”
Section: Bonementioning
confidence: 99%